Igniting the Power of Community The Role of CBOs and NGOs in Global Public Health - Gaist, Paul A.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
Igniting the Power of Community The Role of CBOs and NGOs in Global Public Health Edited by Paul A. Gaist, PhD, MPH Johns Hopkins Bloomberg School of Public Health Igniting the Power of Community: The Role of CBOs and NGOs in Global Public Health introduces readers to the pursuit and potential of community-based organizations and nongovernmental organizations to transform global public health. At a time of unprecedented challenge economic crises, social inequalities, environmental stressors, emerging health threats these organizations are driving change, often being the first to call attention to the issues and increasingly forging significant and sustainable solutions. Igniting the Power of Community demonstrates why understanding the roles of the diverse organizations of this sector is vital to anyone concerned with improving health and public health today. This forward-thinking book explains how citizen sector organizations work, their immediate and long term impact on public health, and the key players and business dynamics involved. A sampling of the coverage: The new era of social entrepreneurship and philanthropy Sustainability in international public health NGOs Front-line perspectives from both well-established and grassroots CBOs Faith-based organizations and public health NGOs and the military: evolving relationships in conflict and disaster zones Understanding the environmental health movement and its impact Whether you are involved in clinical care, health research, public health programs, or policy development and implementation, this book will serve as an invaluable resource in working most effectively with and within these dynamic organizations. "The origins and impacts of health and disease exist in diverse communities throughout the world. Igniting the Power of Community clearly describes the organized response of persons and communities at all levels of society and the challenges they face in reaching their potential to have maximum impact on protecting and preserving the public health. An important book to read."James W. Curran, M.D., M.P.H., Dean, Rollins School of Public Health, Emory University "This book is a guide to understanding, working with, and improving nongovernmental and community-based organizations. For those of us interested in improving the health of populations, Igniting the Power of Community should be required reading."Michael J. Klag, M.D., M.P.H., Dean, Johns Hopkins Bloomberg School of Public Health
Preparing for Action -- A Brief History of CBOs/NGOs in Health and Public Health -- From an Idea to a Sustainable Organization: Getting a Grassroots CBO Off the Ground -- The Importance of Sustainability in International Public Health NGOs -- Donor Organizations: What You Need to Know -- Areas of Action -- Philanthropy and the Culture of Giving: Its Beginnings, Current Character, and Future Expectations -- The Freedom to Innovate: The Contributions of Social Entrepreneurs to the Field of Global Public Health -- Faith-Based Organizations and Public Health -- Disasters and Conflict Zones Around the World: The Roles and Relationships of the Military and Nongovernmental Organizations -- Evidence, Equity, and Economics: Lessons and Challenges of the Environmental Health Movement -- On the Frontline: Community-Based Organizations in Health Research -- Citizens in Action -- YEAH: One Story of Inspiration and Success -- The American Red Cross: Delivering Services and Working with Partners in the USA and Around the World -- CARE: The Contribution of an International NGO to Global Health -- Health Care for the Homeless: Beyond Repairing the Safety Net -- Practical and Pragmatic: Strategically Applying Gender Perspectives to Increase the Power of Global Health Policies and Programs -- (3z(BHappy Healthy Muppets(3y(B: A Look at Sesame Workshop$1 (Bs Health Initiatives Around the World -- Working Across Sectors: Preventing Disease and Promoting Health Through Policy and Practice -- Human Trafficking and Its Public Health Implications -- Healthy Carolinians Microfinancing: Igniting the Power of the Community -- Working Across Borders: Transnational NGOs -- Call to Action -- Players and Pawns: The Current Controversy with and Clampdown on NGOs in Russia -- Community-Based Organizations in the Millennium: Opportunities for Growth, Challenges to Survival -- Global Public Health: Winning the Fight.s
Keywords: Medicine; Public health; Medicine & Public Health; Public Health; Health Promotion and Disease Prevention